If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10m + -5 = 95 Reorder the terms: -5 + -10m = 95 Solving -5 + -10m = 95 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -10m = 95 + 5 Combine like terms: -5 + 5 = 0 0 + -10m = 95 + 5 -10m = 95 + 5 Combine like terms: 95 + 5 = 100 -10m = 100 Divide each side by '-10'. m = -10 Simplifying m = -10
| (1/2-x)2 | | 190=3x^2-2 | | 3x-7=-15x+35 | | 4x-16+12=0 | | 4z+1=2z+7 | | 5x+2(5x-4)=18 | | Cos(35)=2/x | | 4.50=(2x)^2/(0.15-x) | | 0=16t^2+88t | | g(x+1)=5-3(x+1) | | h(x)=2 | | 4x-2=4(x-5) | | 144x^2-36=(12x+6)(12x-6) | | 4cos^2(x)+4sin^2(x)=0 | | tx^2+3x-14=0 | | x-3.1x=14.7+12 | | x-4.8=9 | | 7x+9x+7x=274 | | 4a+5-7= | | 14+2x=180 | | 0=-16t^2+44t-24 | | 14x+7x+9x=137 | | -3(2+5b)= | | 76(-2-3)=19x+6 | | 7-12(x+3)=13-15(2x-5) | | 0=-16t^2+20t+36 | | a/5-15=1 | | 12x-2=36 | | y=2E-05x+1 | | 0=-16t^2+0t+36 | | 3-(-2m)+9-m= | | 2+x(x+2)-3=x^2+2x+1-4 |